Preface: Zooplankton under multiple stressors - Gutierrez, Marìa Florencia (2025)
The present Special Issue, “Zooplanktons Under Multiple Stressors,” covers the impact of various environmental stressors on zooplankton or specific groups within this community. These stressors include land use change, climate change, pollution, and predation, among others. The issue features two bibliographic reviews and seven research papers based on field studies conducted in diverse aquatic systems, including ponds, rivers, streams, and lakes, as well as experimental studies performed in mesocosms.